Аспекты улучшения экологической ситуации литейных цехов - Евтушенко, Наталья Сергеевна; Чунихина, Лидия Николаевна (ГО "СФБЖДЛ", 2016)
Представлен краткий анализ материалов об экологических проблемах литейного производства. Дано описание вредных веществ, которые выделяются в процессе литья и предложены способы уменьшения вредных выбросов.

Article provides a brief analysis of the materials about the ecological problems foundry. The description of the harmful substances that are released during the casting process and suggests ways to reduce harmful emissions foundry.
Aspects of improvement of ecological situation of foundries
Keywords: литейное производство; экологические проблемы; токсичные вещества; улучшение воздушной среды; foundry; ecological problems; toxic substances; improving air quality